47.6k views
1 vote
Help with 6? I really need all correct answers. Please help!

Help with 6? I really need all correct answers. Please help!-example-1

1 Answer

2 votes

Answer:

A

Explanation:

(f - g)(x) = f(x) - g(x)

=
(2x+6)/(3x) -
(√(x)-8 )/(3x)

Since both fractions have a common denominator of 3x, then subtract the numerators leaving the denominator, that is the numerators simplified

2x + 6 - (
√(x) - 8)

= 2x + 6 -
√(x) + 8 = 2x -
√(x) + 14

Hence

f(x) - g(x)

=
(2x-√(x)+14 )/(3x) → A

User Swan
by
5.1k points